1939_04 The Daily Collegian April 1939 - Associated Students of Fresno State::::::::: (Associated Students of Fresno State, Fresno, Calif.)
Daily (except weekends) during the school year. Microfilm. Palo Alto, Calif. BMI Library Microfilms, 1986-